6q22.1 microdeletion and susceptibility to pediatric epilepsy - Szafranski, Przemyslaw (Eur J Hum Genet, 2015)
Genomic copy-number variations (CNVs) constitute an important cause of epilepsies and other human neurological disorders. Recent advancement of technologies integrating genome-wide CNV mapping and sequencing is rapidly expanding the molecular field of pediatric neurodevelopmental disorders. In a previous study, a novel epilepsy locus was identified on 6q16.3q22.31 by linkage analysis in a large pedigree. Subsequent array comparative genomic hybridization (array CGH) analysis of four unrelated cases narrowed this region to ∼5 Mb on 6q22.1q22.31. We sought to further narrow the critical region on chromosome 6q22. Array CGH analysis was used in genome-wide screen for CNVs of a large cohort of patients with neurological abnormalities. Long-range PCR and DNA sequencing were applied to precisely map chromosomal deletion breakpoints. Finally, real-time qPCR was used to estimate relative expression in the brain of the candidate genes. We identified six unrelated patients with overlapping microdeletions within 6q22.1q22.31 region, three of whom manifested seizures. Deletions were found to be de novo in 5/6 cases, including all subjects presenting with seizures. We sequenced the deletion breakpoints in four patients and narrowed the critical region to a ∼250-kb segment at 6q22.1 that includes NUS1, several expressed sequence tags (ESTs) that are highly expressed in the brain, and putative regulatory sequences of SLC35F1. Our findings indicate that dosage alteration in particular, of NUS1, EST AI858607, or SLC35F1 are important contributors to the neurodevelopmental phenotype associated with 6q22 deletion, including epilepsy and tremors.